FfugLen Y Ddelwedd o'r Nofel Gymraeg o Ddechrau'r Chwedegau tan 1990 - Jones, E. (Y Meddwl ar Dychymig Cymreig, 2008)
FfugLen is the Welsh word for fiction but is also a play on the words 'ffug' (meaning fake or false) and 'len' (the prepositive of 'llenyddiaeth' or literature) implying that these images are often ambiguous. This title presents a study of the image of Wales and the Welsh in twentieth-century Welsh-language literature.